The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1109/twc.2018.2876229
|View full text |Cite
|
Sign up to set email alerts
|

Interference Exploitation in Full-Duplex Communications: Trading Interference Power for Both Uplink and Downlink Power Savings

Abstract: This paper considers a multiuser full-duplex (FD) wireless communication system, where a FD radio base station (BS) serves multiple single-antenna half-duplex (HD) uplink and downlink users simultaneously. Unlike conventional interference mitigation approaches, we propose to use the knowledge of the data symbols and the channel state information (CSI) at the FD radio BS to exploit the multi-user interference constructively rather than to suppress it. We propose a multi-objective optimisation problem (MOOP) via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…In addition, they treat the SI signal as an undesired additive distortion. Whereas, it is justified from the information theoretic definition of mutual information that treating the SI term as mere interference will result in a loss of useful information [24], [25]. Moreover, both research studies did not investigate whether the HWIs exhibit symmetric or asymmetric distortion characteristics.…”
Section: A Related Workmentioning
confidence: 99%
“…In addition, they treat the SI signal as an undesired additive distortion. Whereas, it is justified from the information theoretic definition of mutual information that treating the SI term as mere interference will result in a loss of useful information [24], [25]. Moreover, both research studies did not investigate whether the HWIs exhibit symmetric or asymmetric distortion characteristics.…”
Section: A Related Workmentioning
confidence: 99%
“…Note that, w.r.t. [23] here we include the receive beamforming in the MOOP instead of assuming a ZF receiver. It can be observed that, due to the substitution of the conventional downlink SINR constraint with the CI SINR constraint, the constraint B1 is now convex.…”
Section: Moop Based On Constructive Interferencementioning
confidence: 99%
“…Most relevant to the focus of this paper are [21]- [23]. The authors in [21] investigated the power efficient resource allocation for a MU-MIMO FD system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the proposed schemes have been specifically tailored for Phase-Shift Keying (PSK) modulation scenarios, recent works have shown that such concepts can be readily adapted to accommodate CI exploitation in Quadrature Amplitude Modulation (QAM) [40], [41]. In fact, the authors in [42] have proven that the benefits of CI can extend to 16-QAM modulations by allowing the predictable interference at the BS to constructively superimpose with the desired signal at the receiver side.…”
Section: Introductionmentioning
confidence: 99%